2010
DOI: 10.1007/s00221-010-2277-4
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol induced region-dependent alterations of hemodynamic response: implications for the statistical interpretation of pharmacological fMRI studies

Abstract: Worldwide, ethanol abuse causes thousands of fatal accidents annually as well as innumerable social dysfunctions and severe medical disorders. Yet, few studies have used the blood oxygenation level dependent functional magnetic resonance imaging method (BOLD fMRI) to map how alcohol alters brain functions, as fMRI relies on neurovascular coupling, which may change due to the vasoactive properties of alcohol. We monitored the hemodynamic response function (HRF) with a high temporal resolution. In both motor cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…A growing body of evidence shows that many diseases and pathologies -including brain injuries -alter neurovascular coupling and change BOLD signal without necessarily affecting neuronal function Gsell et al, 2000;Krainik et al, 2005;Lindauer et al, 2010;Sakatani et al, 2003Sakatani et al, , 2007. In the same vein, we must also consider that patients with severe brain injuries are usually on several medications, which can also influence neurovascular coupling (Bruhn et al, 2001;Luchtmann et al, 2010;Pattinson et al, 2007;Reinhard et al, 2010). We can attribute changes in BOLD signal to changes in neural activity if and only if signalling and vascular reactivity are not altered; and we can compare between groups (e.g., patients and controls) only if these properties are the same in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence shows that many diseases and pathologies -including brain injuries -alter neurovascular coupling and change BOLD signal without necessarily affecting neuronal function Gsell et al, 2000;Krainik et al, 2005;Lindauer et al, 2010;Sakatani et al, 2003Sakatani et al, , 2007. In the same vein, we must also consider that patients with severe brain injuries are usually on several medications, which can also influence neurovascular coupling (Bruhn et al, 2001;Luchtmann et al, 2010;Pattinson et al, 2007;Reinhard et al, 2010). We can attribute changes in BOLD signal to changes in neural activity if and only if signalling and vascular reactivity are not altered; and we can compare between groups (e.g., patients and controls) only if these properties are the same in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…11–14 The opposite effects of acute alcohol on CBF and CMRglc, on one hand reflect alcohol’s vasoactive effects 15 , and on the other hand reflect the use of alternative energy sources for brain metabolism (e.g., alcohol’s metabolite acetate). 16,17 Specifically, recent work has suggested that biphasic vasoactive properties of alcohol 15 may disrupt the coupling between neuronal activity and CBF. 16 In relation to the association between CMRglc and brain activity during intoxication, our work has suggested that alcohol-induced decreases in glucose metabolism are concurrent with brain-wide increases in acetate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Specifically, recent work has suggested that biphasic vasoactive properties of alcohol 15 may disrupt the coupling between neuronal activity and CBF. 16 In relation to the association between CMRglc and brain activity during intoxication, our work has suggested that alcohol-induced decreases in glucose metabolism are concurrent with brain-wide increases in acetate metabolism. 17 The acetate content in plasma increases during alcohol intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of this approach become clear when investigating subjects with processes that may modify the local HRF or when analyzing data from rest scans (Brown et al, 2001;Moritz et al, 2005;Quigley et al, 2002). It is known that many factors such as age, respiration, disease states, and medications can all affect the shape of the HRF (Bonakdarpour et al, 2007;Luchtmann et al, 2010). ICA can identify temporal signals and spatial networks without utilizing any preformed assumptions about neural responses.…”
Section: Introductionmentioning
confidence: 99%